Proceedings of the Symposium on Eye Tracking Research and Applications 2014
DOI: 10.1145/2578153.2578181
|View full text |Cite
|
Sign up to set email alerts
|

Influence of visual cueing on students' eye movements while solving physics problems

Abstract: Overlaying visual cues on diagrams and animations can help students attend to relevant areas and facilitate problem solving. In this study we investigated the effects of visual cues on students' eye movements as they solved conceptual physics problems. Students (N=80) enrolled in an introductory physics course individually worked through four sets of problems, each containing a diagram, while their eye movements were recorded. Each diagram contained regions that were alternatively relevant to solving the probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…This corresponds with the positive results of hints (Raphael et al 2008), expert modeling (Pedersen and Liu 2002), and feedback (Rouinfar et al 2014) from previous empirical studies. However, the results indicated that providing multiple strategies of scaffolding in one scaffolding system is counter-productive.…”
Section: Implications For Researchsupporting
confidence: 84%
“…This corresponds with the positive results of hints (Raphael et al 2008), expert modeling (Pedersen and Liu 2002), and feedback (Rouinfar et al 2014) from previous empirical studies. However, the results indicated that providing multiple strategies of scaffolding in one scaffolding system is counter-productive.…”
Section: Implications For Researchsupporting
confidence: 84%
“…Studies of problem-based learning in which scaff olding is added by intelligent tutoring systems are not numerous (Belland, Walker, Kim, & Lefl er, 2017). In intelligent tutoring systems, adding is typically initiated by students pushing a hint button to request more support (Girault & d'Ham, 2014;Rouinfar et al, 2014). In addition, as supports are added, the characteristics of scaff olding can be changed from generic to context-specifi c to help students solve a specifi c learning issue at the step or process during which they experience the challenge .…”
Section: Self-directed Learning In Problem-based Learningmentioning
confidence: 99%